The impact of medical tourism on cervical cancer screening among immigrant women in the U.S. - Sou Hyun Jang; Hendrika Meischke; Linda K. Ko (BMC, 2021)
Abstract Background Research on the relationship between medical tourism-traveling abroad for healthcare and cervical cancer screening is lacking. This study examines (1) the association between medical tourism and cervical cancer screening among immigrant women and (2) whether the association varies across years in the U.S. Methods We analyzed the New Immigrant Survey data of immigrant women aged 21-65 (n = 999). The outcome was having had a Pap smear since becoming a permanent resident, and the main predictor was medical tourism. Logistic regressions were conducted. Results Immigrant women who engaged in medical tourism had higher cervical cancer screening rates compared to those who did not engage in medical tourism (84.09% vs. 71.68%). This relationship was statistically significant only among women who have recently immigrated, after controlling for covariates. Conclusions Immigrant women who engaged in medical tourism had 2.18 higher odds of receiving a Pap smear than immigrant women who did not, after controlling for other covariates. Health educators should be aware of the practice of medical tourism and consider providing education on adherence to cancer screening guidelines and follow up abnormal results to ensure that immigrant women receive continuous cancer care.